2020
DOI: 10.1136/thoraxjnl-2019-214077
|View full text |Cite
|
Sign up to set email alerts
|

Macrophage-derived exosomes attenuate fibrosis in airway epithelial cells through delivery of antifibrotic miR-142-3p

Abstract: IntroductionIdiopathic pulmonary fibrosis (IPF) is a progressive fibrosing interstitial lung disease of unknown aetiology and cure. Recent studies have reported a dysregulation of exosomal microRNAs (miRs) in the IPF context. However, the impact of IPF-related exosomal miRs on the progression of pulmonary fibrosis is unknown.MethodsTwo independent cohorts were enrolled at the ambulatory care polyclinic of Liège University. Exosomes from sputum were obtained from 19 patients with IPF and 23 healthy subjects (HS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
87
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 94 publications
(89 citation statements)
references
References 56 publications
1
87
0
1
Order By: Relevance
“…Emerging evidence had indicated exosomes, the paracrine signal mediators, impacted the progression of fibrotic diseases by transferring anti-fibrotic or pro-fibrotic miRNAs to target cells and affected pathological fibrogenesis [ 50 ]. One of the major challenges for synthetic miRNAs was quickly degraded by the high activity of ribonuclease in plasma, but exosome would protect miRNAs from degradation [ 51 , 52 ].…”
Section: Discussionmentioning
confidence: 99%
“…Emerging evidence had indicated exosomes, the paracrine signal mediators, impacted the progression of fibrotic diseases by transferring anti-fibrotic or pro-fibrotic miRNAs to target cells and affected pathological fibrogenesis [ 50 ]. One of the major challenges for synthetic miRNAs was quickly degraded by the high activity of ribonuclease in plasma, but exosome would protect miRNAs from degradation [ 51 , 52 ].…”
Section: Discussionmentioning
confidence: 99%
“…111 A further study by the group showed strong indications that upregulated miR-142-3p, derived from sputum and plasma exosomes of patients with IPF, were of macrophage origin. 110 Guiot et al 110 also found that over expression of miR-142-3p could reduce expression of TGFβ-R1 and ultimately have an antifibrotic effect.…”
Section: Idiopathic Pulmonary Fibrosismentioning
confidence: 98%
“…MiR-144-3p and miR-142-3p also inhibit phosphorylation of the SMAD2 protein in a mouse bleomycin-induced lung injury model [ 21 ]. Moreover, macrophage-derived EVs downregulate the expression of TGFβ receptor 1 (TGFβ-R1) and profibrotic genes in lung epithelial cells and lung fibroblasts through miR-142-3p [ 73 ]. Others showed that IL-1β activation on lung fibroblasts stimulated EV-associated prostaglandin E2 (PGE2) production.…”
Section: Evs In Ild Pathogenesismentioning
confidence: 99%
“…For example, the neutrophil cell line (HL-60) secretes EVs containing miR-1343 that can be taken up by alveolar epithelial cells and lung fibroblasts, further inhibiting TGFβ, a major profibrotic regulatory signaling pathway modulator [ 97 ]. Macrophages are another source of EVs that contain miR-142-3p, which inhibits a profibrotic activation in epithelial cells and lung fibroblasts by downregulating TGFβRI [ 73 ]. The EVs from IL-1β activated human lung fibroblasts contained PGE2 that inhibited myofibroblast differentiation and collagen production, implicating their antifibrotic properties for in vivo testing [ 74 ].…”
Section: Therapeutic Roles Of Extracellular Vesiclesmentioning
confidence: 99%